Physico‐Chemical Processes. (1st October 2014) - Hua, Bin; Xiong, Huixin; Wang, Zhengyang; Yang, John; Zhang, Shichen; Wang, Zhongzhen; Deng, Baolin
Abstract : This review is on the research literature published in 2013 related to the physico‐chemical processes for water and wastewater treatment. The review is divided into seven sections, including coagulation/flocculation, filtration, oxidation, sedimentation, flotation, sorption process: removal of inorganics, and sorption process: removal of organics.